Principles of Protein structure - Schulz, G E Schirmer, R H Cantor, Charles R; Ed (SPRINGER, 1979)
Provides a comprehensive bibliography on protein structure. The authors use the known structures to illustrate the forces, which determine protein structures, the rationale behind many of the features of organization of proteins, and the mechanisms by which proteins perform biological functions.